Progressiveness of Sharia Insurance as A Component of The Islamic Non-Bank Financial Industry in Indonesia - Sanurdi; Rafiqah; Ait Si Ali, Hicham; Fakhrurrazi (State of Islamic Institute Langsa, 2024)
The condition of sharia insurance in Indonesia shows limited development; it ranked fourth and only rose one rank from 2019 as the country with the highest number of operators in the world. The market share of sharia insurance, when compared to conventional insurance, reached 6% at the end of 2020. This study aims to analyze the development of sharia insurance in Indonesia through statistical data analysis of sharia insurance financial performance during the 2018–2022 period. This article is classified as literature research with a qualitative approach. The methodology used is a content analysis study. The results found that sharia insurance in Indonesia experienced asset growth of 3.53%, total gross contribution year-on-year of 16.38%, and continued to record investment results in the 2018–2022 range. The growth was dominated by the capital market sector and the banking sector, which experienced an increase.